2017
DOI: 10.1016/j.juro.2016.07.090
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Stone Recurrence among Children and Adolescents

Abstract: Purpose Kidney stone disease has become increasingly common during childhood and adolescence; however, the rate of symptomatic kidney stone recurrence for pediatric patients is uncertain. Materials and Methods We performed a retrospective cohort study of patients aged 3–18 years without anatomic abnormalities or genetic causes of nephrolithiasis who presented with a first symptomatic kidney stone between 2008 and 2014. We determined recurrence rates of symptomatic nephrolithiasis, defined as a new kidney sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0
3

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 145 publications
(73 citation statements)
references
References 26 publications
0
70
0
3
Order By: Relevance
“…While paediatric urolithiasis remains rare, its incidence is rising [1,2]. Furthermore, for those individuals affected by stone disease, recurrence can occur in up to 50% of cases [3,4]. Therefore, the need to establish and develop effective and safe surgical treatments is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…While paediatric urolithiasis remains rare, its incidence is rising [1,2]. Furthermore, for those individuals affected by stone disease, recurrence can occur in up to 50% of cases [3,4]. Therefore, the need to establish and develop effective and safe surgical treatments is paramount.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Nephrolithiasis is a disorder of mineral metabolism that is associated with increased risk for chronic kidney disease, 4,5 fracture, 6 and hypertension. 5,7 Individuals with nephrolithiasis also have a high risk for recurrent painful kidney stone events, 8,9 some of which require surgery and are associated with increased risk for kidney failure and death. 10 Due the rapid shift in the epidemiology of nephrolithiasis, investigators have focused on identifying novel determinants of kidney stone disease, including antibiotics and their impact on the intestinal and urinary microbiome composition.…”
mentioning
confidence: 99%
“…This study in the same stream with [30] who reported that there is a significant relation between high intake of meat, poultry, fish and kidney stone formation Compared to low intake. Moreover a study done by [31] found that increase animal protein intake are associated with increase excretion of calcium, oxalate, uric acid and decrease excretion of citrate result in risk of stone disease. The current study findings also showed that there was statistical significance difference between kidney stone and higher Cereals and grains intake (χ 2 =8.420, p= .004*).…”
Section: Discussionmentioning
confidence: 99%